Short-term mortality of myocardial infarction patients with diabetes or hyperglycaemia during admission. Issue 9 (1st September 2002) - Sala, J; Masiá, R; González de Molina, F-J; Fernández-Real, J M; Gil, M; Bosch, D; Ricart, W; Sentí, M; Marrugat, J
Abstract : Aim: The hypothesis that patients with hyperglycaemia during admission, regardless of previous diagnosis of diabetes, have worse prognosis than those with normal glucose values is controversial. The objective was to assess the role of hyperglycaemia on short-term mortality after myocardial infarction (MI). Methods and Results: A cohort study nested in a prospective registry of MI patients in the reference hospital of Gerona, Spain was performed. All consecutive MI patients under 75 were registered between 1993 and 1996. Patient and clinical characteristics, including previous diagnosis of diabetes, glycaemia on admission and in the next four days, were recorded. Patients with glycaemia on admission or four day mean glycaemia >6.67 mmol/l were considered hyperglycaemic. The main outcome measure was mortality at 28 days. Of 662 patients with MI included, 195 (29.7%) had previously known diabetes mellitus, but 457 (69.0%) had glycaemia >6.67 mmol/l on admission. Patients with hyperglycaemia on admission were older, more often female, more frequently had a previous diagnosis of diabetes, developed more complications, and had higher 28 day mortality. The effect of admission glycaemia >6.67 mmol/l on 28 day mortality was independent of major confounding factors, particularly previous diagnosis of diabetes (OR=4.20, 95% confidence intervals 1.18 to 14.96). Conclusions: Higher 28 day mortality was observed among MI patients with glycaemia on admission >6.67 mmol/l compared with patients with lower levels, independently of major confounding variables and, particularly, previous diagnosis of diabetes. This early, simple, and inexpensive marker of bad prognosis after MI should prompt the application of more aggressive treatment of MI and risk factors and, probably, of glycaemia during admission.